Can online discussions facilitate deep learning for students in General Education? - Aderibigbe, Semiyu Adejare (Heliyon, 2021)
Studies suggest that online discussions complement teaching and students' learning. However, research also indicates that some tutors and students are uncertain about the value and quality of the learning process in online discussions. The debate and uncertainty necessitate more studies on students' learning quality and depth in online discussions. Therefore, this study aimed to explore how the quality of students' learning and posts are influenced by the deep learning approach in General Education classes through the online discussions. Data collection and analysis were done using both qualitative and quantitative strategies. For the qualitative part, students' posts were retrieved verbatim and mapped deductively with the deep and surface learning approaches, while the number of students' post were collected and analyzed descriptively. The findings indicate that most students' posts are of high quality and are grounded in the deep learning approach through their engagements in online discussions and a reflective assignment. The study concludes that online discussions can foster deep learning if instructors provide students with clear guidelines and reasonable time to engage with colleagues. Online discussions; General education; Constructivism; Students; Instructors